2021
DOI: 10.2478/dim-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Significant Characteristics and Models for Classification of Structure Function of Academic Documents

Abstract: With the increasing abundance of literature resources, how to acquire knowledge elements efficiently and accurately is the key to achieving accurate literature retrieval and utilization of available literature resources. The identification of the structure function of academic documents is a fundamental work to meet the above requirements. In this study, the proceedings of the Association for Computational Linguistics (ACL) conferences are used as the primitive corpus, and the training corpus of chapter catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The F 1 value is 97.50% which is higher than several traditional methods. Ma et al. (2020) hold a similar view and thought that identifying the structure of academic papers was the basis for achieving accurate retrieval of academic papers.…”
Section: Related Workmentioning
confidence: 98%
See 1 more Smart Citation
“…The F 1 value is 97.50% which is higher than several traditional methods. Ma et al. (2020) hold a similar view and thought that identifying the structure of academic papers was the basis for achieving accurate retrieval of academic papers.…”
Section: Related Workmentioning
confidence: 98%
“…The F1 value is 97.50% which is higher than several traditional methods. Ma et al (2020) hold a similar view and thought that identifying the structure of academic papers was the basis for achieving accurate retrieval of academic papers. They found that the section title was more beneficial than the in-section text while identifying the article structure based on 3,992 articles from ACL.…”
Section: Introductionmentioning
confidence: 98%
“…Lu et al ( 2014 ) used vocabulary and sequence annotation methods to identify the structural functions of chapters, but however process for identifying titles containing unknown words still needs to be improved. Bowen Ma shows that the title of a chapter is more beneficial to the identification of the structure-function of academic documents than the in-chapter texts (Ma et al, 2021 ). Bowen Ma finds that compared with the chapter content; the chapter title is more conducive to identifying the structure of academic articles (Ma et al, 2022 ).…”
Section: Reviewmentioning
confidence: 99%
“…words still needs to be improved. Bowen Ma shows that the title of a chapter is more beneficial to the identification of the structurefunction of academic documents than the in-chapter texts (Ma et al, 2021). Bowen Ma finds that compared with the chapter content; the chapter title is more conducive to identifying the structure of academic articles (Ma et al, 2022).…”
Section: Reviewmentioning
confidence: 99%